INTELLECTUAL, POLITICAL, AND ORGANIZATIONAL DISAGREEMENTS INSIDE THE PALESTINIAN NATIONAL LIBERATION MOVEMENT “FATAH” AND THEIR CONSEQUENCES ON THE PALESTINIAN QUESTION, 1965–1986 - Saadia Guenfoud; Djamel Benkhaled (International Journal of Innovative Technologies in Social Science, 2024)
This study is discussing the phenomenon of intellectual, political and organizational disputes that have been accompanying the journey of the Palestinian National Liberation Movement “Fatah,” considering it the most important Palestinian fedayeen organization in terms of armament, organization and numbers. It addressed the internal conditions of the movement and revealed its most significant internal crises. The study concluded that the Palestinian National Liberation Movement “Fatah” carried, since its establishment in the early 1960s, the seeds of disagreement and schism that would grow and bloom at every turning point and impasse the movement—and the Palestine Liberation Organization at large—faced. This affected the absence of a shared vision among its cadres and armed forces, and was responsible for the armed clashes that occurred among its branches spread across the Arab arena. It led to the body of the movement splitting and the birth of new organizations, which increased the number of fedayeen factions on the Palestinian and Arab political and military stage. Ultimately, these disputes widened the circle of Palestinian–Palestinian conflict in all its forms, harming the Palestinian struggle and allowing regional and international actors to meddle in Palestinian internal affairs and exploit them to serve their regional and global policies and agendas.